Effect of bore fluid composition on structure and performance of asymmetric polysulfone hollow fiber membrane contactor for CO2 absorption - Sisakht, Masoud Rahbari (2012)
Porous asymmetric polysolfone (PSf) hollow fiber membranes were fabricated using wet spinning process. Glycerol (4 wt.%) was used as additive. Aqueous solutions of 1-methyl-2-pyrrolidone (NMP) with different composition (0, 50, 70 and 90 wt.% NMP) were used as bore fluid. Distilled water was used to preparing aqueous NMP solutions. Structure and performance of resulting membranes in measuring of surface porosity, pore size, critical water entry pressure (CEPw) and CO2 absorption in hollow fiber membrane contactor were investigated. The cross-section, the inner skin layer and the inner surface of the membranes were examined via scanning electronic microscopy (SEM). Using distilled water as bore fluid provided the membrane structure with a finger-like macrovoids which extend from the inner and outer surfaces of the membranes to the middle of the hollow fiber wall. Other hollow fiber membranes formed with a finger-like structure near the other surface and a sponge-like structure with holes beneath, which resulted in a high CEPw and CO2 absorption rate. In addition, since a mixture of distilled water and NMP was used as the neutral bore fluid, the membranes showed a skinless inner surface. Results of gas permeation tests showed with increasing NMP concentration in the bore fluid the N2 permeance decrease significantly and the wetting resistance decrease slightly. CO2 absorption by distilled water was conducted through the gas–liquid membrane contactors. By employing 90% NMP in the bore fluid, the PSf membrane showed a CO2 flux of approximately 110% higher than the PSf membrane fabricated with distilled water as the internal coagulant at the absorbent velocity of 7.9 × 10−4 m/s.